Modern Imaging Techniques in Cardiomyopathies. Issue 7 (15th September 2017) - Jan, M. Fuad; Tajik, A. Jamil
Abstract : Modern advanced imaging techniques have allowed increasingly more rigorous assessment of the cardiac structure and function of several types of cardiomyopathies. In contemporary cardiology practice, echocardiography and cardiac magnetic resonance imaging are widely used to provide a basic framework in the evaluation and management of cardiomyopathies. Echocardiography is the quintessential imaging technique owing to its unique ability to provide real-time images of the beating heart with good temporal resolution, combined with its noninvasive nature, cost-effectiveness, availability, and portability. Cardiac magnetic resonance imaging provides data that are both complementary and uniquely distinct, thus allowing for insights into the disease process that until recently were not possible. The new catchphrase in the evaluation of cardiomyopathies is multimodality imaging, which is purported to be the efficient integration of various methods of cardiovascular imaging to improve the ability to diagnose, guide therapy, or predict outcomes. It usually involves an integrated approach to the use of echocardiography and cardiac magnetic resonance imaging for the assessment of cardiomyopathies, and, on occasion, single-photon emission computed tomography and such specialized techniques as pyrophosphate scanning.